Asymptotic Spreading for General Heterogeneous Fisher-KPP Type Equations - Berestycki, Henri; Nadin, Grégoire (Memoirs of the American Mathematical Society, 2022)
In this monograph, we review the theory and establish new and general results regarding spreading properties for heterogeneous reaction-diffusion equations: The characterizations of these sets involve two new notions of generalized principal eigenvalues for linear parabolic operators in unbounded domains. In particular, it allows us to show that